YOGA: METODE LATIHAN DAN PENYEMBUHAN HOLISTIK - Ni Wayan Sri Rahayu; I Made Nuhari Anta (Veda Jyotih: Jurnal Agama dan Sains, 2022)
Yoga could be defined as a spiritual science that is currently growing rapidly almost everywhere around the globe. This particular yoga practice, which combines traditional and modern techniques, is intended to enhance all three aspects of physical, mental, and spiritual health in the human body. Asana practice, pranayama exercises, and meditation are the three yoga practices through which these three components can be attained. The third part of Astangga Yoga (the eight stages of doing yoga) is the practice of Asanas or physical movements. Asanas are described as an upright pleasant position. By practicing asanas for 45 minutes in the morning or in the evening, either through Surya Namaskara Yoga movements or individual Asanas movements, one may stretch the muscles, joints, and nerves in the body. The second exercise namely Pranayama, or breathing methods of control; in this situation, proper and good breath control may promote calmness. Respiratory control could also affect an individual’s capacity for controlling their anxiety and handling too much stress. The current condition is able to be obtained due to the breath control that is capable to produce a favorable impact on neurotransmitters, the activity of alpha waves, and the activity of the vagal tone (neurological systems that control the heart, lungs, and gastrointestinal tract). This is therefore capable of producing tremendous usefulness for decreasing passion and providing a sense of calmness. Ability to induce a relaxation state despite undue exertion or pressure. Once the first two exercises are completed successfully, the third practice is meditation, which tries to connect the energy inside humans with the energy of the cosmos or may be viewed as the individual recognizing and comprehending who he/she actually is. Holistic health may be developed or established after these three elements have been attained through yoga practice.